Task-Sharing Between Pediatricians and Non-Physician Healthcare Professionals in Outpatient Child Health Care in Germany: Assessment of Need and Acceptance for Concept Development - Angelika Beyer MSc; Laura Rehner MSc; Wolfgang Hoffmann PhD; Neeltje van den Berg PhD (SAGE Publishing, 2020)
Although pediatricians in Germany work as general practitioners for children, they are planned and trained as medical specialists. In consequence, distances between practices and residences of patients can be very large. The implementation of task-sharing models is a promising option to sustain pediatric outpatient care in rural regions. In this study we assessed the need for and acceptance of delegation of tasks in outpatient pediatric healthcare to non-physician healthcare professionals and developed a task-sharing concept. A standardized questionnaire was developed and addressed a wide range of healthcare professionals. On the basis of the results of the questionnaire and a subsequent workshop involving representatives of the various fields of pediatric care a delegation-concept was developed. A total of 206 questionnaires were answered (response rate: 17%). About 70% of the respondents (n = 145) agreed with the delegation of counseling on prevention, 66% (n = 135) with the delegation of tasks in the transition process into adult medicine. All proposed tasks were conceivable for at least a third of the respondents. Mostly, pediatricians could envision delegation more than the non-physician health care professionals. A three-dimension-delegation-concept was developed: which tasks can be delegated to whom in which setting. Basically, if nurses or medical practice assistants are adequately qualified, all tasks can be delegated to both. The delegation was approved by most of the respondents. Implementation of task-sharing provides a new option to support pediatricians and create better access to outpatient pediatric health care in rural regions. The next step should be the implementation of the delegation concept in pilot projects.